دراسة وصفية على استخدام كتاب العربية بين يديك في تعليم مهارة الكلام لطلاب المستوى المبتدئ بمعهد القرآن واللغة بوغور - Reza, Muhammad Riki (INTIFA: Journal of Education and Language, 2025)
This study aims to explore the role of the book Al-‘Arabiyyah Bayna Yadayk in teaching speaking skills to beginner-level students at Ma'had Al-Qur'an wal Lughah Bogor. The researcher used a qualitative descriptive method through interviews, observation, and documentation. The participants included two students with different levels of speaking ability, the principal of the institute, and an Arabic language teacher. The findings show that Al-‘Arabiyyah Bayna Yadayk greatly contributes to improving students' speaking skills through its various dialogues and oral exercises, which help students use correct sentences, expand their vocabulary, and build confidence in speaking. Teachers also applied interactive teaching strategies such as repetition, imitation, role-playing, and group work, making the lessons more engaging. Despite challenges like limited time and overlapping materials, the book proved effective in achieving language learning goals, and the institute was able to overcome these issues. Therefore, Al-‘Arabiyyah Bayna Yadayk is a valuable educational tool for enhancing speaking skills among beginners, and the researcher hopes this study will support the development of speaking instruction and serve as a useful reference for teachers and researchers interested in this field.